Internet addiction among students of selected schools of Pokhara, Nepal - Singh, Sakun; Shrestha, Sandhya (Journal of Chitwan Medical College, 2021)
Background: Internet is accessed by over billion users worldwide and continues to rise every year. A huge number of these users belong to teenagers and young adults that uses internet on daily basis for different purposes. The present study was conducted with the purpose to assess the internet addiction among adolescence. Methods: A cross-sectional study was conducted among students studying in selected schools of Pokhara, Nepal. A total 144 students were selected as sample using purposive sampling during April/May 2019. Data collection was done using structured demographic proforma, Modified young 20 item internet Addiction Test. Self-administered method was used for data collection. Data were analyzed using descriptive and inferential statistics. Results: The study revealed among the 144 students mean age was 15.52 +1.17, two third 60.7% were from 16-20 years of age, 61.1 % were male, more than half 51.1% were from grade nine and starting mean age of the respondents was 11.78+2.4.Majority 85.4 % were using internet from more than one year,43.8% were spending one to two hour with internet users,65.3% of the respondents were using internet for recreation purpose, all most respondents 96.5 were using internet in home,74.23% were using internet in mobile, starting mean age was 11.78+2.4.More than half 51.2% of the respondents had moderate to severe level of Internet addiction. Conclusions: Study findings shows moderate to severe level of Internet addiction. There was significant association between internet addiction and Internet using year, duration of internet use, spent with internet user and purpose of internet use.